2017
DOI: 10.15436/jfst.2.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Developmental Toxicity Study of HEA-enriched Cordyceps Cicadae Mycelia in Sprague-Dawley Rats

Abstract: ABSTRACT:Background: Cordyceps cicadae (C. cicadae) has been used in traditional medicine and is presently being developed for therapeutic purposes and dietary supplements. One of its effective bioactive ingredients is N

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Aside from its efficacy, the safety of C. cicadae mycelia is also of primary importance. Numerous studies have shown that C. cicadae mycelia is safe to use for ethnomedicinal and culinary purposes . In the 90‐day subchronic toxicity study, the no‐observed‐adverse‐effect level of C. cicadae mycelia was estimated to be greater than 2 g kg −1 body weight in male and female Sprague–Dawley rats .…”
Section: Resultsmentioning
confidence: 99%
“…Aside from its efficacy, the safety of C. cicadae mycelia is also of primary importance. Numerous studies have shown that C. cicadae mycelia is safe to use for ethnomedicinal and culinary purposes . In the 90‐day subchronic toxicity study, the no‐observed‐adverse‐effect level of C. cicadae mycelia was estimated to be greater than 2 g kg −1 body weight in male and female Sprague–Dawley rats .…”
Section: Resultsmentioning
confidence: 99%
“…Treatment with HEA (20 and 40 mg/kg) for six weeks reduced blood glucose in alloxan-induced diabetic rats [ 9 ]. The safety of C. cicadae mycelium has been evaluated in rat, rabbit, pig, and mouse models, as well as humans [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The C. cicadae mycelia are parasitic toward specific hosts, such as Cicada flammata Distant, Platypleura kaempferi Fabricius, Crytotympana pustulata Fabricious, Platylomia pieli Kato, and Oncotympana maculatieollis Motsch (Zeng et al., 2014 ). The cicadae flower has been used as traditional Chinese medicine (not only in China but also in Japan and Taiwan) for at least 1,600 years to treat fatigue, night perspiration, fever, childish convulsion, palpitation, epilepsy, and many eye diseases (Kuo et al., 2002 ; Li et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…HEA is an adenosine derivative; it is associated with control of the brain and coronary circulation and has anti‐inflammatory activity (Deng et al., 2020 ; Lu et al., 2015 ). Also, HEA has also been reported to have sedative–hypnotic activity (Chen et al., 2015 ; Li et al., 2017 ). The yield of C. cicadae collected in the field is low and unstable and easily contaminated with soil mold before drying.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation